Adaptation of Transcendence at Work Measuring Instruments for Muslim Employees - Cahyono, Aryo Bima Fathoni; Kanya, Nita; Kadiyono, Anissa Lestari (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Transcendence in the workplace is an individual's sense of connectedness to colleagues and the larger community through the perception of work as a service for the common good that generates a sense of completeness and fulfillment. To analyze it, a measuring instrument is needed that can measure this. This study aims to adapt transcendence at work measuring instruments and test the psychometric properties to be tested on Muslim workers in Indonesia. This measuring instrument has been confirmed suitable for use in Hindu workers in India, but there have been no studies that test this measuring instrument on Muslim workers. The concept of transcendence which is quite attached to the teachings of Islam makes researchers interested in conducting this research. The transcendence at work measuring instrument developed by Khari and Sinha consists of 3 dimensions and 12 items that can measure transcendence in the workplace. The process of adapting measuring instruments refers to the International Test Commission. This study involved 200 Muslim workers in Indonesia. The reliability tests used are alpha Cronbach and CFA to measure construct validity. It was found that all items in the transcendence at work measuring instrument can measure transcendence in the workplace in Muslim workers in Indonesia.